2017
DOI: 10.1590/1980-5373-mr-2016-0751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Organo-Modified Montmorillonite on the Barrier Properties of PET Nanocomposites Using a Polyester Ionomer as a Compatibilizing Agent

Abstract: Poly(ethylene terephthalate)/organically modified montmorillonite (PET/o-Mt) nanocomposites were prepared via melt intercalation in a twin-screw extruder using a polyester ionomer (PETi) as compatibilizer. The o-Mt content used was 0, 1, 3 or 5 wt% and the compatibilizer/o-Mt mass ratio was 0/1, 1/1 or 3/1. The main objective was to study the effects of the addition of o-Mt and compatibilizer on the barrier properties of PET/o-Mt nanocomposites. The nanocomposites showed a significant reduction in CO 2 permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Moreover, the oriented nanocomposite fiber showed significant improvement in tensile stiffness, maximum strength, and Young's modulus. Vidotti et al [41] investigated the effect of addition of polyester ionomer (PETi) as a compatibilizer to PET/Cloisite® 20A. The study showed that the compatibilizer can promote the intercalation and exfoliation of nanoclay in a polymer matrix resulting in the reduction of carbon dioxide and moisture permeability of up to 50% and 30%, respectively, from pristine PET [41,42].…”
Section: Polymers For Nanoclay Composites In Food Packagingmentioning
confidence: 99%
“…Moreover, the oriented nanocomposite fiber showed significant improvement in tensile stiffness, maximum strength, and Young's modulus. Vidotti et al [41] investigated the effect of addition of polyester ionomer (PETi) as a compatibilizer to PET/Cloisite® 20A. The study showed that the compatibilizer can promote the intercalation and exfoliation of nanoclay in a polymer matrix resulting in the reduction of carbon dioxide and moisture permeability of up to 50% and 30%, respectively, from pristine PET [41,42].…”
Section: Polymers For Nanoclay Composites In Food Packagingmentioning
confidence: 99%
“…From Table 4, it can be observed that the glass transition temperatures of PET and PET copolymers decrease with the increase in clay content; Vidotti et al 9 had reported this effect for PET/Cloisite 20A composites. Thus, the present data show that this relation between clay content and T g is the same for PETI and PETINPG.…”
Section: Dsc‐initial Investigationsmentioning
confidence: 88%
“…From Figures 4 and 5 and Table 5, it can be observed that, for both matrices and both kinds of crystallization, an increase in clay content leads to an increase in maximum crystallization rate and an anticipation of crystallization (shifts to higher temperatures in melt crystallization and to lower temperatures in cold crystallization). Vidotti et al, 9 who prepared PET/clay composites, also reported an increase in melt crystallization temperature (T c ) and a decrease in cold crystallization temperature (T cc ) with the addition of clay; this was attributed to the nucleating effect of clay. According to Perez and Alvarez, 32 many researchers have demonstrated that clay nanoparticles have nucleating and accelerating effects on polymer crystallization through different experimental parameters, such as crystallization temperature, maximum crystallization rate, effective energy barrier and crystallization half‐time, not to mention kinetic parameters.…”
Section: Dsc‐initial Investigationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these, the most widely used polymers are polyethylene terephthalate, nylon, polystyrene, polyolefins, polylactide, polyamide, polyimides, epoxy resins polyurethane and ethylene-vinyl alcohol (Bumbudsanpharoke and Ko 2019), while the commonly used nanoclays includes montmorillonite and aluminasilicate layered clay (Silvestre et al 2011). Vidotti et al (2017) studied that the addition of polyester ionomer compatibilizer in polymer clay composite resulted in exfoliation and intercalation of nanoclays that reduces up to 30% and 50% of moisture and carbon dioxide permeability, respectively. Xie et al (2012) investigated that combining low density polyethylene (nonpolar, hydrophobic polymer) with organo-montmorillonite improved the moisture barrier, which could be reduced if the contents of organomontmorillonite exceed a certain limit.…”
Section: Improved Polymer Nanoparticles Packagingmentioning
confidence: 99%